Well-defined calcium compound catalyzes trimerization of arylisocyanates into 1,3,5-triarylisocyanurates - Kumar, Rohit; Sharma, Vishal; Jain, Shailja; Sharma, Himanshu; Vanka, Kumar; Sen, Sakya S. (ChemCatChem, 2022)
We report the synthesis of a calcium complex (2) bearing a tetradentate monoanionic ligand with a diaminoethane core and phenolate and pyridine peripheral donors. Single crystal X-ray studies on 2 revealed that LiI was also co-crystallized, leading to a four-membered ring with four different elements. 2 was found to be an efficient catalyst for the cyclotrimerization of a variety of aromatic isocyanates under mild conditions.
Keywords: calcium; Cyclotrimerization; Isocyanurates; Tetradentate ligand

C=C insertion over N=C=O of allyl isocyanate into the Ge-Si bond of a germylene - Ajithkumar, V. S.; Khilari, Nripen; Ghanwat, Pratiksha B.; Koley, Debasis; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2025)
Two isocyanates are reacted with the germylene, PhC(NtBu)(2)Ge-Si(SiMe3)(3) (1). Phenyl isocyanate undergoes catalytic cyclotrimerization with 1 leading to 1,3,5-triphenyl isocyanurate (2), while allyl isocyanate undergoes both cyclotrimerization and the C=C bond insertion between the Ge-Si bond. The constitution of 3 is determined by single-crystal X-ray studies. The contrasting reactivity pattern is explained by comprehensive density functional theory studies.
Keywords: Cyclotrimerization; Density functional theory; Germylene; Insertion; isocyanates